Factors affecting career choice among undergraduate students in Universiti Utara Malaysia, Sintok, Kedah - Afidatul Asma, Hassan (2015)
One of the critical aspects of an individual’s life is career choice as a career chosen will determine the role pattern need to be played by the individual in the society in the future and the career choice is one of the important processes in life. The aim of this study is to investigate the factors that influencing the career choice of the students. This study is focus on undergraduate students in university Utara Malaysia, Sintok, Kedah. Undergraduate students were chosen because right upon graduation, they were the one who will be dealing with the decision on career choice. A total number of 315 students responded to the questionnaire. Statistical Package software for Social Science (SPSS) Version 22.0 was used to analyze the collected data. Reliability analysis, multiple regressions and correlation were applied to this study. Pearson correlation analysis results showed that the influence of family, personal interests, and economic considerations have a positive relationship to career choices. Moreover, the results of regression analysis showed that the personal interests exerted great influence on the choice of a career compared to family influence and economic considerations. Recommendations for further study in the future in order to investigate other important factors that influence students' career choices.